2018
DOI: 10.5312/wjo.v9.i10.203
|View full text |Cite
|
Sign up to set email alerts
|

Screw placement is everything: Risk factors for loss of reduction with volar locking distal radius plates

Abstract: AIMTo determine factors correlated with postoperative radial shortening in patients with distal radius fractures treated with volar locking distal radius plates.METHODSA total of 250 patients with a distal radius fracture stabilised with volar locking plates between January 2010 and December 2014 were included in a multicentre retrospective cohort study. We measured the distance of the distal locking screws to the joint line immediately postoperatively and then measured radial shortening after six to eight wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…A greater dosage of ALN has been proven to be more effective in qualitative microtomographic analysis of bone repair. This could be seen through the greater number of trabeculae and the decreased spacing between the trabeculae in the 3 mg/kg group (6,16,33). More bone density suggests that a higher dosage in uences bone quality, which encouraged the researchers in this experiment to use both 1 mg/kg and 3 mg/kg.…”
Section: -Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A greater dosage of ALN has been proven to be more effective in qualitative microtomographic analysis of bone repair. This could be seen through the greater number of trabeculae and the decreased spacing between the trabeculae in the 3 mg/kg group (6,16,33). More bone density suggests that a higher dosage in uences bone quality, which encouraged the researchers in this experiment to use both 1 mg/kg and 3 mg/kg.…”
Section: -Discussionmentioning
confidence: 94%
“…When combined with anabolic-active drugs, ALN signi cantly improves bone mineral density and reduces bone fracture (3,8,14,15). Previous research has shown that short-term ALN treatment also improves bone repair around implants installed in the tibias of osteoporotic rats, demonstrating the drug's potential therapeutic effect (16,17).…”
Section: -Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Quotation error Unsubstantiated 'Patients treated with VLDRP still often have their wrists immobilised postoperatively, rather than being allowed to use as tolerated' (Drobetz et al, 2018) 'Delivering full-scale multi-centre randomised controlled trials (RCT) in trauma and orthopaedics cost large amounts of funding (typically in excess of £1 M) and large amounts of time (typically 4-5 years)' (Kearney et al, 2019) 'Reoperation rates after VLP have been reported as up to 15% in some studies and 6% for CRPP' (Liao et al, 2018) '. .…”
Section: Error Typementioning
confidence: 99%
“…Biomechanical studies comparing volar fixed-angle locking plates with that of conventional dorsal plates report volar fixed-angled plates to be superior in terms of their strength. Dorsal plating of distal radius has not garnered much popularity due to fact that, inspite of dorsal plating, the volar collapse of fracture occurred [8,[9][10][11][12][13] .…”
Section: Case Reportmentioning
confidence: 99%